1933
DOI: 10.1111/j.1469-1809.1933.tb02094.x
|View full text |Cite
|
Sign up to set email alerts
|

A Co‐operative Study of the Habits, Home Life, Dietary and Family Histories of 450 Cancer Patients and of an Equal Number of Control Patients

Abstract: The articles published by the Annals of Eugenics (1925–1954) have been made available online as an historical archive intended for scholarly use. The work of eugenicists was often pervaded by prejudice against racial, ethnic and disabled groups. The online publication of this material for scholarly research purposes is not an endorsement of those views nor a promotion of eugenics in any way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

1948
1948
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 0 publications
0
24
1
Order By: Relevance
“…Ovarian cancer gave the strongest relation, which remained significant after control for other dietary variables. Case-control studies have previously shown inconsistent results for this cancer (Cramer et al, 1984;La Vecchia et al, 1987b;Mori et al, 1988) For breast cancer, some case-control studies (Hislop et al, 1986;Talamini et al, 1984) but not all (Lubin et al, 1981;La Vecchia et al, 1987a) have shown positive associations with milk intake. The interaction between milk and alcohol consumption seen in one study (Le et al, 1986) was not supported by our data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian cancer gave the strongest relation, which remained significant after control for other dietary variables. Case-control studies have previously shown inconsistent results for this cancer (Cramer et al, 1984;La Vecchia et al, 1987b;Mori et al, 1988) For breast cancer, some case-control studies (Hislop et al, 1986;Talamini et al, 1984) but not all (Lubin et al, 1981;La Vecchia et al, 1987a) have shown positive associations with milk intake. The interaction between milk and alcohol consumption seen in one study (Le et al, 1986) was not supported by our data.…”
Section: Discussionmentioning
confidence: 99%
“…At an early stage in cancer epidemiology, Stocks and Karn (1933) examined the relation between milk intake and overall cancer incidence in a case-control study. Crude analyses indicated an inverse association with cold milk.…”
mentioning
confidence: 99%
“…Many studies have been conducted comparing the diets of patients with gastric cancer and those of controls variously selected (Stocks and Karn, 1933;Wynder et al, 1963;Acheson and Doll, 1964;Higginson, 1966). These have not given any strong and consistent indications to incriminate any one item of diet.…”
Section: Discussionmentioning
confidence: 99%
“…382 patients gave histories of 452 parents or siblings having suffered from cancer, so that in 70 instances (3.3 per cent) more than one relative was affected. There were 17 instances of both parents having died of cancer amongst 1589 patients of known family history, or 1 in 93; the expectation of this occurring by chance is 1 in 151; Stocks and Karn (1933) found the expected frequency of this event for cancer of all regions to be 1 in 180, the numbers involved being 364 fathers and 323 mothers. As no information about family history was available for 25.4 per cent of the patients, it is impossible to draw definite conclusions from the figures.…”
mentioning
confidence: 99%